2022
DOI: 10.1111/apt.17125
|View full text |Cite
|
Sign up to set email alerts
|

Treatment patterns of anti‐tumour necrosis factor‐alpha and prognosis of paediatric and adult‐onset inflammatory bowel disease in Korea: a nationwide population‐based study

Abstract: Summary Background The global prevalence of inflammatory bowel disease (IBD) is increasing. However, population‐level data are scarce for Asian populations. Aims To outline and compare paediatric and adult IBD incidence and prevalence data in Korea, describe prescription patterns, and analyse outcomes of anti‐tumour necrosis factor (anti‐TNF) use in a nationally representative cohort Methods IBD was identified based on the presence of Rare and Intractable Disease diagnosis codes for Crohn's disease (CD) and ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
(52 reference statements)
1
2
0
Order By: Relevance
“…I thank Dr. Burisch for his editorial, 1 which highlighted important findings of our data provided by the National Registry 2 . My co‐authors and I agree with his appraisal of the content of our article.…”
supporting
confidence: 55%
“…I thank Dr. Burisch for his editorial, 1 which highlighted important findings of our data provided by the National Registry 2 . My co‐authors and I agree with his appraisal of the content of our article.…”
supporting
confidence: 55%
“…Choe and colleagues have reported on the incidence and prevalence of IBD in Korea between 2006 and 2015. 1 They also described the treatment patterns and surgery rates during that period using the Korean nationwide patient registry. The authors made several interesting observations.…”
mentioning
confidence: 99%
“…In Crohn’s disease, early and effective use of TNF-α blockers also prevented the development of disease complications, for example, strictures or penetrating ulcerations and disease progression [ 28 ]. A Korean study revealed that early anti-TNF-α medication led to a lower risk of surgery during disease progression [ 30 ]. In another study, early admission of biologics significantly reduced the risk of penetrating complications but not stenosing complications [ 31 ].…”
Section: Early and Effective Use Of Tnf-α Blockers Prevents Disease P...mentioning
confidence: 99%